Exploring the World: A Journey Through Culture and Nature - Saurav Chandra Talukder (Lembaga Bale Literasi, 2025)
This study explores the interconnection between cultural identity and ecological consciousness within the context of global tourism, drawing from case studies in Bhutan, New Zealand, and Indonesia. Through thematic analysis using NVivo 12 software, five key themes emerged: community participation, indigenous leadership, governance frameworks, ethical tourism practices, and transformative travel experiences. Findings revealed that active community involvement is fundamental to sustainable tourism, as local engagement helps preserve cultural heritage and ecological integrity. Indigenous knowledge systems, particularly among the Māori in New Zealand and ecovillage communities in Indonesia, shaped authentic tourist experiences and promoted environmental stewardship. Bhutan’s application of the Gross National Happiness philosophy demonstrated how culturally aligned governance can support low-impact tourism that benefits both hosts and visitors. Additionally, the integration of ethical standards such as those set by the Global Sustainable Tourism Council (GSTC) was associated with reduced cultural commodification and environmentally responsible practices. Tourists participating in culturally immersive and nature-based experiences reported heightened environmental awareness and cross-cultural empathy, suggesting that tourism can serve as a catalyst for global citizenship and personal transformation. Despite these strengths, the research also highlighted ongoing challenges including over-tourism, climate change, and unequal benefit distribution. These findings call for a shift from sustaining to regenerating cultural and natural resources, emphasizing participatory policymaking, ethical education, and inclusive governance. Ultimately, the study affirms that the thoughtful integration of culture and nature can redefine tourism as a transformative, ethical, and sustainable global practice